Cardiovascular Changes Associated with Hypertensive Heart Disease and Aging - Saheera, Sherin; Krishnamurthy, Prasanna (Cell transplantation, 2020)
Cardiovascular diseases are the leading cause of mortality and morbidity worldwide and account for more than 17.9 million deaths (World Health Organization report). Hypertension and aging are two major risk factors for the development of cardiac structural and functional abnormalities. Hypertension, or elevated blood pressure, if left untreated can result in myocardial hypertrophy leading to heart failure (HF). Left ventricular hypertrophy consequent to pressure overload is recognized as the most important predictor of congestive HF and sudden death. The pathological changes occurring during hypertensive heart disease are very complex and involve many cellular and molecular alterations. In contrast, the cardiac changes that occur with aging are a slow but life-long process and involve all of the structural components in the heart and vasculature. However, these structural changes in the cardiovascular system lead to alterations in overall cardiac physiology and function. The pace at which these pathophysiological changes occur varies between individuals owing to many genetic and environmental risk factors. This review highlights the molecular mechanisms of cardiac structural and functional alterations associated with hypertension and aging.